Relationship between endothelial shear stress, plaque burden and stenosis severity and their comparative performance in predicting impaired coronary vasodilation by pet myocardial perfusion imaging. (25th November 2020) - Anagnostopoulos, C; Kalykakis, G; Antonopoulos, A; Siogkas, P; Manniittyy, T; Kafouris, P; Liga, R; Giannopoulos, A; Scolte, A; Kaufmann, P; Pelosi, G; Parodi, O; et al.
Abstract: Background: Advances in CTCA imaging enable assessment of coronary plaque burden, a predictor of myocardial perfusion abnormalities and more recently, with the use of computational fluid dynamics (CFD) of endothelial shear stress (ESS), an established contributor to atherosclerotic plaque development and progression. Purpose: To investigate the relationship of local endothelial shear stress (ESS) and plaque burden (PB) between them and with stenosis severity as well as their comparative performance in predicting impaired coronary vasodilating capability assessed by PET myocardial perfusion imaging (MPI). Methods: 49 patients (29 males, mean age 65.3±6.3 years, intermediate pre-test likelihood of coronary artery disease, CAD), who underwent PET-MPI with 15O-water or 13N-ammonia and CTCA were included. PET was considered abnormal when >1 contiguous segment showed both stress Myocardial Blood Flow ≤2.3 mL/g/min and Myocardial Flow Reserve ≤2.5 for 15O-water or <1.79 mL/g/min and ≤2.0 for 13N-ammonia respectively. On CTCA, stenosis (sten) severity was classified as: <30%, 31–50%, 51–70% and 71–90%. CFD were applied to every vessel, assuming a mean pressure of 100 mmHg as the inlet boundary condition and a coronary velocity profile of 1 ml/sec as the outlet. ESS was calculated for the full length of a stenosis (total), as well as in the proximal (prox), minimum lumen area (MLA) and distal (dist) stenotic segments. Atherosclerotic PB was defined as lesion plaque volume/lesion vessel volume ×100. Results: 85 coronary vessels were evaluated. There was a positive correlation between ESS and PB (r(total)=0.544, r(prox)=0.528, r(MLA)=0.529, r(dist)=0.474, p<0.001 for all). All ESS indices and PB increased progressively with stenosis severity compared to segments with a <30% stenosis (p≤0.004 for all comparisons). ESS indices and PB were also higher in lesions demonstrating impaired vasodilating capacity compared to those without (p≤0.02 for all comparisons, figure 1). All ESS indices performed equally with PB and sten >50% in predicting an abnormal PET MPI, (AUC: from 0.682 to 0.780, p-diff >0.5 for all comparisons). The pairwise combination of sten >50% with the ESS segments, except the distal one, increased the predictive ability of the model over stenosis alone (AUC (sten >50% + ESS(total)) = 0.80, AUC (sten >50% + ESS(prox)) = 0.797, AUC (sten >50% + ESS(MLA)) = 0.822, p-diff ≤0.01 for all comparisons, AUC (sten >50% + ESS(dist)) = 0.768, p-diff=0.07). Conclusion: There is a low to moderate positive association between lesion plaque burden and ESS indices. Like PB, ESS increases progressively with stenosis severity and is higher in lesions paired with abnormal PET results. ESS is a moderate predictor of impaired vasodilating capability, performing equally with PB and stenosis severity. The addition of ESS to stenosis severity can improve prediction of an abnormal PET result. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This study is co-financed by Greece and the European Union (European Social Fund-ESF) through the Operational Programme "Human Resources Development, Education and Lifelong Learning 2014-2020" in the context of the project "Assessment of coronary atherosclerosis: a new complete, anatomo-functional, morphological and biomechanical approach" and from p-Med GR 5002802